Sumur Gumuling dalam Cerita Lisan Masyarakat - purwanti, dwi (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
The Gumuling Well Tourism Site is part of the historical site of the Islamic Mataram kingdom in Yogyakarta which contains the significance of the development of the dynamics of the socio-cultural life of the people in the Pleret region, Bantul. Therefore, the Sumur Gumiling site deserves to be studied to understand the significance of the site to art, social, cultural and community life. This research uses the value function theory developed by Finnegan. Meanwhile, the method of collecting data is through field studies with observation, observation, recording, recording, and in-depth interviews. The data analysis method was adopted by conducting data transcription, refinement, and analyzing to reach a conclusion. The results of this study indicate that the Sumur Gumiling site has the value of an oral tradition that functions to regulate life in the area around the site. Myths and oral traditions are sources of conventional law that are capable of regulating society to comply with strategic arrangements for environmental conservation. In addition, the existence of the site is used as a sign of the preservation of art and oral traditions in the community.